NUNO GRANDE (ed.) - O ser Urbano: Nos caminhos de Nuno Portas - Monclús, Javier (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2014)
NUNO GRANDE (ed.) O Ser Urbano: Nos caminhos de Nuno Portas / The Urban Being: on the trails of Nuno Portas Lisboa: Imprensa Nacional-Casa da Monea, 2012, 639 págs. Idioma: portugués e inglés